Bicuspid aortic valve is associated with less coronary artery calcium and coronary artery disease burden by computed tomography. (14th October 2021) - Barbieri, F; Bleckwenn, S; Stoessl, L; Plank, F; Beyer, C; Gollmann-Tepekoeylue, C; Holfeld, J; Senoner, T; Bonaros, N; Schachner, T; Dichtl, W; Feuchtner, G
Abstract: Background: Bicuspid aortic valve (BAV) is associated with genetic defects (NOTCH 1, GATA 5 mutations) and aortopathy. Differences in flow pattern and a genetic predisposition could also affect coronary arteries. Purpose: To assess the coronary artery calcium score (CACS) and coronary artery disease (CAD) burden by coronary computed tomography angiography (CTA) in patients with BAV stenosis, as compared to those with tricuspid aortic valve (TAV) stenosis. Methods: 47 patients with congenital BAV (68.9 years±12.9, 38.3% females) who underwent cardiovascular CTA for TAVR planning were matched with 47 TAV patients for age, gender, smoking, arterial hypertension, dyslipidemia, diabetes, body-mass-index and chronic kidney disease. The coronary artery calcium score (CACS) (Agatston Units=AU) and coronary stenosis severity by CTA (CADRAD:<25% minimal, <50%milde, 50–70%moderate, >70/%severe) were quantified. Results: The coronary artery calcium score (CACS) was lower in BAV (237.4 vs. 1013.3AU; p<0.001), and coronary stenosis severity was less (CAD-RAD:p<0.001) as compared to patients with TAV. More patients with BAV had CACS zero (27.7% vs. 0%, p<0.001). The majority (68.1%) of patients with BAV had no or non-obstructive CAD but only 25.5% of tricuspid (p<0.001). Obstructive CAD (>50% stenosis) by CTA was more frequently observed in TAV patients (68.1%; p<0.001). There were no differences in statin use and NOAC, and other co-morbidities such as AF and COPD. Conclusion: Patients with BAV have markedly less coronary artery calcium load and yielded less severe coronary stenosis. CTA succeeds to rule out obstructive CAD in the majority of patients with BAV, with adherent implications for TAVR planning. Funding Acknowledgement: Type of funding sources: None.